Acceptance of sustainable agricultural practices: the case of crop farmers - D’Silva, Jeffrey Lawrence; Man, Norsida; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman (Science Publications, 2011)
Problem statement: Agriculture for numerous years has been a source of income generator that offered wide opportunities for employment and enhancing the socio-economic status of mankind in many countries. Without doubt acceptance of agricultural sustainable practices will bring much benefit to the farming community especially in the long run to overcome the scarcity of resources and continuous income. Aim of this study was to determine contract farming entrepreneurs’ acceptance of sustainable agricultural practices and the issues involved in their level of acceptance. Approach: This is a qualitative study and the data was collected from a focus group discussion on seven contract farming entrepreneurs in Cameron Highlands, Malaysia. The researchers played the role as the instrument during the data collection process and an interview guide assisted researchers to obtain objectives of the study. Data obtained from the respondents was recorded and eventually transformed into verbatim transcripts for the process of data analysis. Results: It was identified that contract farming entrepreneurs have a sound knowledge on sustainable agricultural practices and they belief it is vital for mankind. However, their level of acceptance is still not significant as they perceive that they still need much support from the relevant agriculture agencies. Conclusion/recommendation: It is suggested that all concerned parties should make the necessary sacrifices and put in more effort in ensuring that contract farming entrepreneurs will eventually embrace sustainable agricultural practices that will bring benefit to the present and future generations.